2008
DOI: 10.1038/leu.2008.347
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles in differentiating leukemia cells induced by methyl jasmonate are similar to those of cytokinins and methyl jasmonate analogs induce the differentiation of human leukemia cells in primary culture

Abstract: Jasmonates are potent lipid regulators in plants that play pivotal roles in their biological activities. Methyl jasmonate (MJ) is very effective at inducing the myelomonocytic differentiation of human myeloid leukemia HL-60 cells. We examined the gene expression profiles associated with exposure to MJ using cDNA microarrays, and compared the results with those obtained with other inducers of differentiation, such as all-trans retinoic acid (ATRA), 1a,25-dihydroxyvitamin D 3 (VD 3 ), isopentenyladenine (IPA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…In the past decade, several groups have demonstrated that members of jasmonate family and their synthetic derivatives exhibit anti-cancer activity on other kinds of tumor cells, including lung cancer [26], colon cancer [27], glioma [28], cervical cancer [29,30], neuroblastoma [12,13], and myeloid leukemia [31,32]. To date, several mechanisms have been proposed to explain the anti-cancer effects of jasmonates, including induction of severe ATP depletion via mitochondrial perturbation [33], induction of re-differentiation via mitogen-activated protein kinase activity [31], induction of a significant decrease in survivin levels via the β-catenin/T-cell factor pathway [27], and induction of apoptosis via pro-apoptotic proteins of the Bcl-2 family [34], opening the mitochondrial permeability transition pore complex [11] and activation of extrinsic apoptotic pathway [35].…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, several groups have demonstrated that members of jasmonate family and their synthetic derivatives exhibit anti-cancer activity on other kinds of tumor cells, including lung cancer [26], colon cancer [27], glioma [28], cervical cancer [29,30], neuroblastoma [12,13], and myeloid leukemia [31,32]. To date, several mechanisms have been proposed to explain the anti-cancer effects of jasmonates, including induction of severe ATP depletion via mitochondrial perturbation [33], induction of re-differentiation via mitogen-activated protein kinase activity [31], induction of a significant decrease in survivin levels via the β-catenin/T-cell factor pathway [27], and induction of apoptosis via pro-apoptotic proteins of the Bcl-2 family [34], opening the mitochondrial permeability transition pore complex [11] and activation of extrinsic apoptotic pathway [35].…”
Section: Discussionmentioning
confidence: 99%
“…JAs also increased the life span of T-cell lymphoma-bearing mice [17]. Thereafter JAs, including MJ and related synthetic analogs, were found to inhibit in vitro cancer cell proliferation and to induce cell death in other human and murine cancer cell types [16, 1924], including human breast [15, 25], cervix [2629], colon [30, 31], colorectal [32], gastric [33], hepatoma [34, 35], lung [19, 36, 37], lymphoma [15, 17, 18, 38], melanoma [15, 30, 39, 40], myeloid leukemia [41, 42], neuroblastoma [43–45], prostate [15, 46–48], and sarcoma [49] cancer cells (Table 1). Other results have shown that JAs and their synthetic derivates exerted selected cytotoxic effects in vivo towards metastatic melanoma [21, 39] and inhibited angiogenesis at high doses (it was the reverse at low doses) in the chorioallantoic membrane (CAM) of chicken embryo [40] (Table 2).…”
Section: Effects Of Jasmonates On Mammalian Cancer Cellsmentioning
confidence: 99%
“…MJ (0.4 mM) stopped the growth of these blast cells and promoted their differentiation to normal cells, as deduced from the expression of markers of differentiation such as NBT reduction (for myelomonocytic differentiation), morphological differentiation into granulocytes, and expression of CD14 (monocyte-specific) and CD15 (granulocyte-specific) surface antigens [41]. MJ induced also the expression of the Ca 2+ -binding protein S100P in these cells, reported to be linked to induction of differentiation (Table 1) [42]. …”
Section: Effects Of Jasmonates On Mammalian Cancer Cellsmentioning
confidence: 99%
“…S100P also expressed in leukemia (Tsumura et al 2009) with unknown functions. In oral cavity squamous cell carcinoma expression of S100P was associated with anoikis resistance (Kupferman et al 2007).…”
Section: S100p In Different Cancersmentioning
confidence: 99%